Assessment of green tea reductive degradation of halogenated solvents. (March 2021) - Wu, Siang Chen; Wang, Chi-Wei; Hsu, Li-Hsin; Liang, Chenju
Abstract: Green tea (GT) leaves can be brewed into a solution rich in polyphenols that serve as effective reducing agents, and the complexes formed by combining green tea with ferrous ion (GT/Fe(II)) can provide an elevated reduction potential. The dissociated GT polyphenols at alkaline pH can dramatically increase the formation of GT/Fe(II) complexes. This experimental work evaluated the reductive reactivity of alkaline GT solution and GT/Fe(II) complexes (at pH 10) on 14 halogenated volatile organic compounds (VOCs). Carbon tetrachloride (CT), with a highest carbon oxidation state (COS) of IV, was observed to be degradable by the alkaline GT solution, while all others proved ineffective. The GT/Fe(II) complexes are very reactive and capable of degrading halogenated methanes, ethanes, and ethenes, in which chemical structures exhibit zero or positive COS values, and the chlorine or bromine atom is bonded at the saturated carbon atom, such as CT, chloroform, bromoform, dibromomethane, 1, 1, 1-trichloroethane, and 1, 1, 1, 2-tetrachloroethane. The linear free energy relationship (LFER) approach was used to determine the overall reduction potentials ( E H 0 ) of the alkaline GT solution and GT/Fe(II) complexes, which were found to be −0.131 V and −0.368 V, respectively. These findings demonstrated that GT/Fe(II) complexes exhibit the potential to remediate halogenated contaminants and the E H 0 information obtained in this study may serve as a reference in determining probable reactivity that contributes to degradation of environmental contaminants. Graphical abstract: Image 1 Highlights: Alkaline green tea (GT)/Fe 2+ complexes produce an elevated reduction potential. The E H 0 of alkaline GT and GT/Fe 2+ are −0.131 V and −0.368 V, respectively. The alkaline GT/Fe 2+ degrade halogenated compounds with zero or positive carbon oxidation state. The liquid alkaline GT/Fe 2+ mixture is suitable for subsurface injection. Soil may serve as a natural source of mineral-associated Fe(II) in forming complexes with GT.